Exploring The Main Character's Life Experience in Albert Camus’ The Guest Through Ideational Meaning - Ayuningtias, Diah Ikawati (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2025)
This study investigates how ideational meaning is realized to represent the main character’s life experience in the short story The Guest. It applied Halliday’s concept of Systemic Functional Linguistics, focusing on the transitivity system in ideational metafunction. Using qualitative methods, this study analyzed the clauses in the short story to identify the process types used in the clauses produced by the narrator and the main character of the short story. The result of the analysis showed that the types of process found were material process, mental process, verbal process, existential process, and behavioral process; while relational process was not found in the data. Among the process types, the existential process is the most dominant. The dominant use of existential clauses implies that the writer highlights the main character’s life experience of being lonely. In addition, the absence of relational process indicates that the characteristics of the main character is less described.